Desain Jaringan Irigasi Pipa pada Lahan Datar (Studi Kasus : Petak Tersier Pasir Salam 3 Kiri, Daerah Irigasi Panulisan – Cilacap) - Dadan Rahmandani; Joko Triyono; Dadang Ridwan (Balai Teknik Irigasi, 2014)
The main problem of the application of pressurized pipe irrigation on flat land is not enough energy, so it may cause problem during the operation of the network. Basically, the flow in the pipe can be designed as open flow, so energy requirement can be reduced. However, the application of pipe irrigation system has not been widely studied so it can not be applied to the field scale. This study aims to create a network of pipe irrigation design by gravity with open flow. The research was done by designing pipe irrigation on flat land in Pasir Salam 3 kiri tertiary area. Afterwards the analysis and evaluation of the design requirements was performed in order to get technical feasibility of implementation. As the results, the diameter of the primary pipelines ranging from 8 inches (200 mm) to 10 inches (250 mm) at a flow rate of 0.35 m/s to 0.50 m/s. While the diameter of the secondary and tertiary pipelines between 1 inch (25 mm) to 6 inches (150 mm) with a flow velocity of 0.25 m/s to 0.46 m/s. These results indicate that the design of the application of irrigation pipe networks on flat land in Pasir Salam 3 kiri tertiary area in the Panulisan Irrigation Area was technically feasible considering the results of hydraulic calculation. Thus the water can flow by gravity at velocity ranging from 0.25 to 0.5 m/s and energy availability 0.09 m larger than requirement.